Estudo de moléculas efetoras da resposta imune celular e humoral em pequenos ruminantes contra Corynebacterium pseudotuberculosis como marcadores em ensaios de imunodiagnóstico - Rebouças, Miriam Flores (2013)
Corynebacterium pseudotuberculosis is the etiologic agent of caseous lymphadenitis (CLA), a chronic disease that affects goats and sheep, characterized by granuloma formation in subcutaneous and internal lymph nodes. CLA causes significant economic losses in commercial goat herds; the best procedure to avoid spread of this disease is elimination of infected animals. Secreted antigens from T1 strain bacteria grown in brain heart infusion (BHI) broth were tested in an indirect ELISA system to determine if this system could be used to identify specific immunoglobulins against C. pseudotuberculosis. The electrophoretic profile of the BHI antigen was analyzed, as well as the recognition pattern by CLA infected sheep sera. The ELISA results were compared to Multiplex PCR assay and IFN-gamma production. The ELISA was able to discriminate between negative and positive animals, with a sensitivity of 89% and a specificity of 99%, and a large difference between positive and negative optical density values. When this assay was compared with other immunological and molecular methods, it was found only two discrepant results among thirty-two samples. We concluded that an ELISA using secreted antigens from C. pseudotuberculosis T1 strain growth in BHI broth culture would be a reliable tool for the serodiagnosis of caseous ymphadenitis in sheep.